The effect of online customer reviews and online customer ratings on hotel room booking with trust as intervening variable - Sihotang, Ruth Helen Aprita; Tobing, Fenny BNL; Mangani, Ktut Silvanita (Technium Social Sciences Journal, 2021)
This study aims to determine the effect of online customer reviews and online customer ratings on purchase intent (hotel room booking) with trust as an intervening variable at Hotel-X in East Jakarta, Indonesia. The data collected using questionnaires distributed to 105 respondents. The sampling method used is nonprobability sampling with an accidental sampling technique. The data is analysed using Partial Least Square (PLS). The results of the study show that online customer reviews and customer trust have a significant and positive effect on hotel room booking. Online customer ratings have a significant and positive effect on hotel room booking, as well as on customer trust. However, trust variable insignificantly affects the hotel room booking. The results explain that the customers of Hotel-X have already put their trust in the hotel. However, the hotel still has to focus on online customer reviews and ratings to increase its room booking